Switchable cyclopalladation of substrates containing two directing groups: on the way to non-symmetrical [2.2]-dipalladaparacyclophanes - Korábková, Tereza; Bartáček, Jan; Marek, Lukáš; Hanusek, Jiří; Růžička, Aleš; Váňa, Jiří (Royal Society of Chemistry, 2023)
Simple switching of the site-selectivity of C-H activation reactions of substrates containing multiple directing groups is particularly important for the so-called late stage functionalization synthetic approach. In this work, we verified the possibility of achieving this by adding acids of different strengths. Using a substrate containing two differently strong (and basic) directing groups, the influence of the addition of acids on the regioselectivity of the C-H activation step of the reaction with palladium acetate was thoroughly studied. The addition of no or weak acids results in cyclopalladation being controlled by a stronger directing group. However, the addition of a strong acid causes protonation of this group and the reaction is then controlled by a weaker directing group. Finally, this approach enables double C-H activation leading to a unique class of compounds: "non-symmetrical" [2.2]-dipalladaparacyclophanes.
Přepínatelná cyklopalladace substrátů obsahujících dvě řídící skupiny: na cestě k nesymetrickým [2.2]-dipaladaparacyklofánům
Keywords: cyclopalladation; [2.2]-dipalladaparacyclophanes; C–H activation; cyklopalladace; [2.2]-dipalladaparacyklofany; C–H aktivace